Analysis of the Use of Hospital Management Information Systems with Jobs to be Done to Increase Innovation Simplifying Administrative Processes at CHP Hospitals - Christiana Indrawati (Journal La Bisecoman, 2024)
The Hospital Management Information System (HMIS) must be developed and implemented in every hospital, in accordance with Minister of Health Regulation Number 82 of 2013, to provide the best service to the Indonesian public, the quality of hospital services must be continuously improved. The management of patient information, data, data processing, and all activities related to a good hospital depend heavily on this. It is important to understand how the implementation of the Hospital Management Information System can improve healthcare service standards in Indonesia after its implementation. Thirty-two samples were used in this study, and SEM-PLS data were analyzed using the Jobs To Be Done approach. The findings indicate that human, organizational structure, and system usage within the Hospital Management Information System (HMIS) can enhance healthcare technology innovation by simplifying administration in hospital services.